2020
DOI: 10.1002/jlb.1ab0120-548r
|View full text |Cite
|
Sign up to set email alerts
|

TCR-α/β CD4− CD8− double negative T cells arise from CD8+ T cells

Abstract: The cellular origin of CD4− CD8− (double negative, DNT) TCR‐α/β+ T cells remains unknown. Available evidence indicates that they may derive from CD8+ T cells, but most published data have been obtained using cells that bear an invariant transgenic T cell receptor that recognizes an Ag that is not present in normal mice. Here, we have used complementary fate mapping and adoptive transfer experiments to identify the cellular lineage of origin of DNT cells in wild‐type mice with a polyclonal T cell repertoire. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 31 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…Previous research indicates that DN T cells are important members of both innate and adaptive immunity (32). However, our current understanding of DN T cells remains limited (33). Some postulate their potential regulatory functions, albeit with comparatively weak immunosuppressive abilities (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that DN T cells are important members of both innate and adaptive immunity (32). However, our current understanding of DN T cells remains limited (33). Some postulate their potential regulatory functions, albeit with comparatively weak immunosuppressive abilities (34).…”
Section: Discussionmentioning
confidence: 99%
“…DN T cells in the periphery are unable to proliferate and mainly converted from CD8 + T cells. They can re-express CD8 when lymphocytes are reduced ( 38 ). This is consistent with our observation in the UMAP plot that DN T cells were closer to CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work we have shown that exposure of CD8 + T cells to self-antigen induces an inactivation program that includes the downregulation of CD8 expression (25)(26)(27). Because we never observed CD8 downregulation during in vitro activation and CD8 loss was only observed in tissues locally expressing the cognate antigen (25), we hypothesized that repetitive encounter with antigen -as occurs in vivo during self-antigen encounter-may play a role in this process and that signaling through Fas or FasL may regulate CD8 loss.…”
Section: Discussionmentioning
confidence: 99%
“…A wealth of evidence indicates that DN T cells derive from CD8ab + T cells: (a) CD8 + and DN T cells share Vb usage and CDR3 sequences (19); (b) mice deficient in b2-microglobulin or MHC-I molecules have reduced numbers of DN T cells (20)(21)(22); (c) the Cd8a locus is hypomethylated in DN T cells, indicating previous transcriptional activity (23,24); (d) CD8 + T cells lose CD8 when they encounter cognate antigen presented as self (25,26); (e) DN T cells can upregulate CD8 when they undergo homeostatic proliferation under lymphopenia (27). Importantly, generation of DN T cells is not limited to situations in which Fas/ FasL function is compromised, as an increased abundance of DN T cells has been reported in a number of chronic inflammatory conditions that include systemic lupus erythematosus (15), primary Sjögren's syndrome (28), and psoriasis (29).…”
Section: Introductionmentioning
confidence: 99%